Análise de um compensador estático paralelo monofásico visando a melhoria do fator de potência - Andrade, Adson íkaro Silva Leite de (2011)
This work consists of developing a control system power factor through the use of a parallel active filter. To this end, the control system of the filter is composed of an outer voltage loop and an inner current loop, based on PI controllers. For its development, it was observed that the application of parallel active filters offered by the literature, where it was realized that this type of filter is often used to correct the power factor for the development of control technique were made in modeling system and their analysis in steady state, after, the modeled system, the controllers were implemented and validated by numerical simulation using a test bench where he was led via DSP algorithm implemented PWM technique to control and command keys potency.